“Listen to the science!”—The role of scientific knowledge for the Fridays for Future movement - Soßdorf, Anna; Burgi, Viktor (Frontiers in Communication, 2022)
The Fridays for Future movement (FfF) has drawn a lot of public and academic attention in recent years. So far, studies investigated the organization, mobilization and motives of the movement from different perspectives as well as the relevance of science for FfF. Mostly from an external perspective researchers looked at the types of science communication and its reception by the audience (i.e. framing theory). In this paper, we combine theories of science communication with the resource mobilization approach in social movement studies and thereby develop a theoretical framework for the analysis of the use of scientific knowledge by climate movements. We focus on the resource mobilization theory (RMT) and the notion of activists as alternative science communicators. RMT emphasizes the role of resources and organization to explain the success of social movements. Specifically, we regard legitimacy as a moral resource and analyze the importance of communication of climate scientific knowledge for FfF as a political movement. We argue that a climate movement like FfF relies on climate scientific knowledge which serves as a moral resource when climate activists refer to it to legitimate their claims. Empirically, we draw on a survey of more than 500 FfF activists in Germany, that was conducted as a mixed method study in 2020 and 2021. Our objective is to close a gap on the relevance of science for FfF activists from the inner perspective. Following the research question “How and why is scientific knowledge being used by FfF activists to mobilize people?” the findings indicate a rather strategic use of scientific knowledge as an end in itself within the movement. Unsurprisingly, we see that individual strategic use of scientific knowledge within the movement corresponds with the belief that FfF should include scientific knowledge in the general communication strategy of FfF. Moreover, our data shows that activists overwhelmingly derive their goals from scientific knowledge and reject the idea that science could be used imprecisely in order to attain their goals. These learnings shed more light on the understanding of the use of science as a moral resource within climate movements like FfF.